Triglycerides and total serum cholesterol in rotator cuff tears: do they matter?. Issue 13 (8th April 2009) - Longo, U G; Franceschi, F; Spiezia, F; Forriol, F; Maffulli, N; Denaro, V
Abstract : Objective: In this study, the serum triglycerides and total serum cholesterol levels in patients with rotator cuff tear were determined. Design: Frequency-matched case-control study. Setting: University teaching hospital. Participants: 240 individuals who were operated on at our institution were included in the study. 120 patients (45 men and 75 women; mean age 64.86 years, range 40 to 83 years) who underwent arthroscopic repair of a rotator cuff tear were included in group 1. 120 patients (45 men and 75 women; mean age 63.91 years, range 38 to 78 years) who underwent arthroscopic meniscectomy for a meniscal tear and had no evidence of shoulder pathology were included in group 2 (control group). These patients were frequency-matched by age (within 3 years) and sex with patients of group 1. Main outcome measures: Measurement of serum triglyceride and total cholesterol concentrations. Results: When comparing the two groups, there was no difference either in serum triglyceride concentration or total serum cholesterol concentration. Conclusions: There appears to be no association between serum triglyceride concentration and total serum cholesterol concentration in rotator cuff tears.